Genetics and breeding for resistance against four leaf spot diseases in wheat (Triticum aestivum L.) - Gupta, Pushpendra Kumar; Vasistha, Neeraj Kumar; Singh, Sahadev; Joshi, Arun Kumar (Frontiers in Plant Science, 2023)
In wheat, major yield losses are caused by a variety of diseases including rusts, spike diseases, leaf spot, and root diseases. The genetics of resistance against all these diseases have been studied in great detail and utilized for breeding resistant cultivars. The resistance against leaf spot diseases caused by each individual necrotroph/hemibiotrophic involves a complex system involving resistance (R) genes, sensitivity (S) genes, small secreted protein (SSP) genes, and quantitative resistance loci (QRLs). This review deals with resistance for the following four-leaf spot diseases: (i) Septoria nodorum blotch (SNB) caused by Parastagonospora nodorum; (ii) Tan spot (TS) caused by Pyrenophora tritici-repentis; (iii) Spot blotch (SB) caused by Bipolaris sorokiniana and (iv) Septoria tritici blotch (STB) caused by Zymoseptoria tritici.